Transcultural pedagogies for multilingual classrooms responding to changing realities in theory and practice - Zaidi, Rahat 1969-; Boz, Umit; Moreau, Eve (New perspectives on language and education, 2024)
"This book explores the ways in which transcultural pedagogies can support learning and literacies in critical, creative and socially just ways, highlighting research initiatives from across the globe. Chapters present innovative perspectives for language/literacy education focusing on Indigenous, plurilingual and digital literacies, among others"--